Pengaruh Struktur Modal, Rasio Likuiditas Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan Property & Real Estate Yang Terdaftar Di Bei Periode 2019-2022 - Novia Damayanti; Ayesha Alika Putri; Lia Uzliawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The author conducted this study with the aim of seeing how capital structure, liquidity, and company size affect the financial performance of a company. This study covers property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2022. 20 eligible real estate and property companies were selected through purposive selection method. To obtain accurate research results, the data was processed using multiple linear regression analysis. According to the analysis, capital structure has an influence on the company's financial performance; liquidity ratio does not affect the company's financial performance; and company size affects the company's financial performance. Keywords: Liquidity Ratio, Capital Structure, Company Size, and Company Financial Performance